Readiness of and barriers for community pharmacy professionals in providing and implementing vaccination services - Wondim Ayenew; Yeniewa Kerie Anagaw; Liknaw Workie Limenh; Wudneh Simegn; Gizachew Kassahun Bizuneh; Teshome Bitew; Tefera Minwagaw; Ayelign Eshete Fitigu; Misganaw Gashaw Dessie; Getahun Asmamaw (BMC, 2024)
Abstract Background Community pharmacy professionals are essential for healthcare delivery, particularly for administering vaccination services. However, there is a lack of substantial evidence documenting their role in vaccination within Ethiopia. Objectives This study aimed to assess community pharmacy professionals' readiness to provide vaccination services, identify barriers hindering the implementation of these services, and determine factors influencing the provision of vaccination services by community pharmacy professionals. Methods A cross-sectional study was conducted among community pharmacy professionals in Debre Markos and Injibara Town from April 15 to May 13, 2024. The data were collected using a structured questionnaire, and descriptive statistics were used to analyze the findings. Results The study revealed that a significant majority of community pharmacy professionals perceived that they had adequate vaccine knowledge and were easily accessible to the community. However, barriers such as lack of regulation, time constraints, workload concerns, patient trust issues, and infrastructure challenges hinder the implementation of vaccination services. Factors influencing the provision of vaccination services included the need for enhanced education and training, financial reimbursement, patient demand, infrastructure improvements, collaboration with other healthcare providers, and pharmacists' special interest in vaccination. Conclusions Community pharmacy professionals exhibit readiness to provide vaccination services. However, significant barriers such as regulatory constraints, time pressures, workload concerns, patient trust issues, and infrastructure challenges hinder their full participation. Addressing these barriers and leveraging pharmacists' expertise is essential for optimizing service delivery and improving public health outcomes. Advocating for policy changes, developing comprehensive training programs, establishing clear guidelines, investing in infrastructure improvements, conducting public awareness campaigns, and fostering collaboration with other healthcare providers are recommended to facilitate the provision and implementation of vaccination services by community pharmacy professionals in Ethiopia.